2010
DOI: 10.1074/jbc.m109.076919
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTSL-6 Is a Novel Extracellular Matrix Protein That Binds to Fibrillin-1 and Promotes Fibrillin-1 Fibril Formation

Abstract: ADAMTS (A disintegrin and metalloproteinase with thrombospondin motifs)-like (ADAMTSL) proteins, a subgroup of the ADAMTS superfamily, share several domains with ADAMTS proteinases, including thrombospondin type I repeats, a cysteine-rich domain, and an ADAMTS spacer, but lack a catalytic domain. We identified two new members of ADAMTSL proteins, ADAMTSL-6␣ and -6␤, that differ in their N-terminal amino acid sequences but have common C-terminal regions. When transfected into MG63 osteosarcoma cells, both isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 61 publications
2
125
0
Order By: Relevance
“…These proteins are localized in connective tissues, including the skin, aorta, and perichondrocytes. Among the ADAMTSL6 family, ADAMTSL6␤ has been shown to associate with fibrillin-1 microfibrils through its direct interaction with the N-terminal region of fibrillin-1 and thereby promotes fibrillin-1 matrix assembly in vitro and in vivo (17). These findings suggest a potential clinical application of ADAMTSL6␤ as a novel MFS therapy by promoting fibrillin-1 microfibril assembly and regulating TGF-␤ activation.…”
Section: Marfan Syndrome (Mfs)mentioning
confidence: 81%
See 1 more Smart Citation
“…These proteins are localized in connective tissues, including the skin, aorta, and perichondrocytes. Among the ADAMTSL6 family, ADAMTSL6␤ has been shown to associate with fibrillin-1 microfibrils through its direct interaction with the N-terminal region of fibrillin-1 and thereby promotes fibrillin-1 matrix assembly in vitro and in vivo (17). These findings suggest a potential clinical application of ADAMTSL6␤ as a novel MFS therapy by promoting fibrillin-1 microfibril assembly and regulating TGF-␤ activation.…”
Section: Marfan Syndrome (Mfs)mentioning
confidence: 81%
“…Expression and Purification of Recombinant Adamtsl6␤-The expression and purification of recombinant Adamtsl6␤ was performed using 293F cells (Invitrogen) and nickel-agarose (Qiagen, Hilden, Germany) as described previously (17). Briefly, pSecTag2A containing an Adamtsl6␤ segment fused with Myc and His tags at its C terminus was transfected into 293F cells, which were cultured for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, ADAMTSL4 mutations occur in recessively inherited isolated ectopia lentis (31,32), and ADAMTS17 mutations result in ectopia lentis in dogs (33) and a WMS-like syndrome in humans (15). Recently, it was shown that ADAMTSL6 was capable of enhancing fibrillin-1 assembly into ECM (34).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are localized in connective tissues, including the skin, aorta and perichondrocytes. Among ADAMTSL6, ADAMTSL6β has shown to associated with fibrillin-1 microfibrils through its direct interaction with the N-terminal region of fibrillin-1 and promotes fibrillin-1 matrix assembly in vitro and in vivo [43]. These findings suggest a potential clinical application of ADAMTSL6β as a novel MFS therapy by promoting fibrillin-1 microfibril assembly and regulating TGF-β activation.…”
Section: Adamtsl6β Serves As a Novel Molecules That Regulate Microfibmentioning
confidence: 82%